Students' Perception Towards The Use of Google Form In English Online Learning - linda, Selindah Rahmawati; Nurchaerani, Meiyanti (EDUCATE : Journal of Education and Culture, 2024)
This study was a qualitative study that explained the perception of Junior High School in West Jakarta in using Google Form app as the English assessment tool. This research aimed to know the students’ experience and the quality using Google form during online learning which conducted at Junior High School in west jakarta with 22 students as the sample and the data were collected by interviewing, and distributing questionnaires. They were asked to fill out a questionnaire and tiga of them were invited to participate in semi-structured interviews. The questionnaire and interview questions totaled 10 questions, each categorized based on the TAM (Technology Acceptance Model), namely perception of usefulness, perception of convenience, perception of intention, and perception of attitude. The results of this study indicate that second grade Junior High School students were found to have more positive perceptions than negative perceptions in the use of Google Form as a tool for assessing student assignments in students' English learning.